An Analysis Of Cross-Cultural Communication Through Asian Player In Genshin Impact - Dewa Bagus Dwi Cancerli Ananta; Ni Ketut Sri Rahayuni; Nissa Puspitaning Adni (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This study aimed to analyze the assumption of similarities in English language through some Asian player of the game and language differences from the game chat. In order to analyze both the assumption of similarities in English language and language differences, this study used a descriptive qualitative method, taking multiple steps of playing and communicating together with some Asian player, taking several screenshots of the game chat. According to Genshin Impact’s producer interview video, Asian Genshin Impact player had different expressions in the conversation such as vocabulary, utterance and even had different cultural background from where they live. Finally, because this is related to the world of fantasy games, the researcher invites readers to include participation to increase the effectiveness of communication between fellow players to support the development of English in the world and in anticipation of persuade young generations and general people to learn more their background culture.